Solidifying the minority high school student pathway: evidence from the health professions recruitment and exposure program - Affini, Murtala I.; Diaz, Ashley; Dolan, Daniel J.; Fletcher, Symphony; Hasnain, Isra; Selkridge, Isaiah; Washington, Stephanie; Pratt, Abdullah (Frontiers in Public Health, 2024)
Purpose The objective of this report is to provide longitudinal insights on the impact of a health professions exposure program for high school students of underrepresented backgrounds in medicine. Context Medical students at the University of Chicago reviewed data from their chapter of the Health Profession Recruitment and Exposure Program (HPREP) from 2016–2021 to discover trends in enrollment. This data is documented in the context of the program's mission to increase awareness of health disparities, the success of prominent alumni, and recent community efforts post-COVID-19 pandemic. Findings Two hundred and ninety-nine high school students participated in the University of Chicago HPREP program between 2016 and 2021. Participants ranged in age from 12 to 18 years (mean = 16, SD = 1) and 74% (n = 222) were female students. Of 252 respondents, 58% (n = 147) identified as Black or African American, 31% (n = 77) identified as Latinx or of Hispanic origin, and 10% (n = 24) identified as another race or as bi-racial. Ten or fewer black male students participated in the program every year, including the 2020–2021 year in which 61 students participated. Conclusions HPREP has played an important role in shaping the face of health care, especially in Chicago. The data suggests significant increases in the number of underrepresented minority women becoming physicians and serving Chicago communities in the next decade. Pathway programs for underrepresented students in medicine should be strategic in recruiting and educating future health professionals based on future workforce needs.